Conflicts of interest among authors of the ESC guidelines for the diagnosis and treatment of acute and chronic heart failure between 2012 and 2021. (3rd October 2022) - Schneider, B; Stoellberger, C
Abstract: Background: In 2011, the Institute of Medicine (IOM) published standards for developing trustworthy clinical practice guidelines recommending that "Whenever possible guideline development group members should not have conflicts of interest (COIs)... Members with COIs should represent not more than a minority of the guideline development group members. The chair or cochair should not be a person with COIs." Purpose: Aim of this study was to assess if the standards of the IOM have influenced the development of the heart failure guidelines of the European Society of Cardiology (ESC) published between 2012 and 2021. Methods: From the ESC homepage, the declarations of COIs of task force members (TFM) and reviewers of the guidelines for the diagnosis and treatment of acute and chronic heart failure from 2012, 2016 and 2021 were retrieved. The number of COIs was assessed for each version of the guideline. Results: Regarding the 2012 guidelines, 24/26 TFM (92%) indicated any COI (range 1–36). Overall, 249 COIs were reported (10.4±7.3 per member). 20/26 TFM (77%) received direct personal payments (8.0±6.6 COIs per member, range 1–28). The chairperson declared 8 COIs. Among the reviewers, 32/38 (84%) indicated any COI (8.1±5.9 COIs per reviewer, range 1–29). Regarding the 2016 guidelines, 19/21 TFM (90%) indicated any COI (range 1–35). Overall, 250 COIs were reported (13.2±9.9 per member). 17/21 TFM (81%) received direct personal payments (10.4±7.4 COIs per member, range 1–28). The chairperson declared the second most COIs (n=33) and the co-chairperson the fourth most COIs (n=21). Among the reviewers, 67/87 (77%) indicated any COI (8.1±7.3 COIs per reviewer, range 1–31). In 2021, 28/31 TFM (90%) indicated any COI (range 2–54). Overall, 391 COIs were reported (13.9±13.8 per member). 23/31 TFM (74%) received direct personal payments (9.7±7.5 COIs per member, range 1–29). The chairperson declared 5 COIs. Among the reviewers, 91/117 (78%) indicated any COI (4.8±4.3 COIs per reviewer, range 1–20). Conclusion: Despite the recommendations of the IOM, the proportion of TFM and reviewers of the ESC heart failure guidelines with COIs remains high in 2021 (90% and 78%, respectively). Overall, the number of COIs of the TFM have increased from 2012 to 2021, and direct personal payments to the TFM remained at a high level. Since COIs can influence healthcare decision makers and may consciously or unconsciously influence choices made throughout the guideline development process, the ESC should follow the standards of the IOM. Funding Acknowledgement: Type of funding sources: None.